2008
DOI: 10.1007/s12182-008-0006-4
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of internal-wave and internal-tide deposits and their hydrocarbon potential

Abstract: The study of internal-wave and internal-tide deposits is a new research fi eld on sedimentology during the last ten years. Deep-water traction currents induced by internal waves and internal tides are developed on the modern sea fl oor, which can form not only all kinds of small scale and dispersal deepwater traction currents deposits, but also large-scale sediment wave in km-size scale. In this paper, the concepts and features of internal waves and internal tides in oceanography are introduced, and the charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The identified tidalites in three depositional systems are compared, based on structural, textural, and architectural elements, through the following sections. [38] suggested that bidirectional cross-laminations or cross-beds, flaser, wavy, and lenticular beds are normally observed in tide deposits. Nevertheless, Mulder et al [39] believed that these sedimentary structures can be formed by turbidity and contour currents too.…”
Section: Discussionmentioning
confidence: 99%
“…The identified tidalites in three depositional systems are compared, based on structural, textural, and architectural elements, through the following sections. [38] suggested that bidirectional cross-laminations or cross-beds, flaser, wavy, and lenticular beds are normally observed in tide deposits. Nevertheless, Mulder et al [39] believed that these sedimentary structures can be formed by turbidity and contour currents too.…”
Section: Discussionmentioning
confidence: 99%
“…Some well-known sediment wave fields were reinterpreted as internal tidal deposits because of the aforementioned reasons. This concerns in particular the Rockall Trough sediments waves (He et al, 2008), the Gulf of Valencia sediment waves (Ribó et al, 2016), as well as within ancient onshore outcrops, with the introduction of the "internalite" term (e.g. Bádenas et al, 2012).…”
Section: Sediment Wave Developmentmentioning
confidence: 99%
“…One of the most fulfilling aspects of working on an exploration team in the petroleum industry is that geologists and geophysicists can propose hypotheses (prospects) and then test their models with the drill bit. We defined prospects based solely on two-dimensional seismic data and geologic concepts (Dunham and McKee, 2001;McKee and Dunham, 2004) and tested our models with exploration wells. Repeated tests of our Kutei Basin hypotheses led to discoveries at the Gendalo, Gandang, Gula, Gada, Gehem, and Ranggas prospects ( Figure 1).…”
Section: John B Dunham and Arthur Sallermentioning
confidence: 99%
“…Our 2006 publication is based on the successful efforts of exploration teams that used geologic concepts to make significant deep-water discoveries in the Kutei Basin (Dunham and McKee, 2001;McKee and Dunham, 2004;Saller et al, 2004Saller et al, , 2008b). Shanmugam's (2013) contention that his alternative view might have "surprising economic consequences in real-world petroleum exploration" (p. 832) is not supported by any similar exploration success (Figure 1).…”
Section: John B Dunham and Arthur Sallermentioning
confidence: 99%